PENINGKATAN IMPULSIF BUYING BERBASIS POSITIVE EMOTION, SHOPPING LIFE STYLE DAN HEDONIC MOTIVATION - Mohammad Sunarmahdi Wiryowidagdo; Tatiek Nurhayati (Jurnal Ekonomi dan Bisnis, 2016)
This study aimed to analyze the increase in impulse buying based on positive emotion, life styleand hedonic shopping motive in Paragon Mall Semarang The study population was a visitorParagon Mall Semarang. The sampling technique uses accidental sampling technique, which isa technique of making it by chance encountered and suitable for research, obtained the numberof samples of 100 people. Analysis tools is the path analysis, which previously tested thevalidity and reliability as well as the classical assumption. The results showed that the hedonicmotive significantly affect life style shopping. Hedonic motive has a significant positive effect onimpulse buying. Possitive emotion has a significant influence on impulse buying. Shopping lifestyle has a possitive influence significantly to impulse buying. Possitive emotion to become anintervening variable between hedonic motive and impulse buying. Shopping life style to becomean intervening variable between hedonic motive against impulse buying.Keywords: Hedonic motive, possitive emotion, life style shopping, impulse buying.